The Successful of Artificial Insemination in Bali Cow in Muaro Jambi Regency, Jambi Province - Supriyono Supriyono; Adlin Yulianto; Yeni Karmila (Fakultas Pertanian Universitas Muara Bungo, 2021)
The successful implementation of the artificial insemination (AI) program is a Measurement of the amount reproductive efficiency value that achieved. The value of the efficiency of the successful of artificial insemination (AI) can be assessed by measuring the rate per pregnancy or Service per Conception (S/C), calving distance or Calving Interval (CI) and pregnancy rate or Conception Rate (CR). This research has been carried out in Muaro Jambi Regency from September 11, 2021 to October 01, 2021. This study aims to determine the success of artificial insemination (AI)) in Bali cow in Muaro Jambi Regency and to determine Service Per Conception (S/C), Conception Rate (CR), and Calcing Interval (CI). This research was conducted using a survey method where the sampling method (respondents) was purposive sampling of respondents who has the criteria, namely respondents who had mother cows who had given birth at least 2 times to breeders in Jambi Luar Kota District, Muaro Jambi Regency and were married by artificial insemination (AI). The changes observed were Service per Conception (S/C), calving interval or Calving Interval (CI) and pregnancy rate or Conception Rate (CR). The data obtained were processed. The results showed that the successful of artificial insemination (AI) in Muaro Jambi Regency in the form of Service per Conception (S/C) which was 1,58, calving interval (CI) of 14,05 months and pregnancy rate or Conception Rate (CR). ) ) of 56,14%. It can be concluded that the successful of Synthetic Insemination (SI) in Muaro Jambi Regency can be categorized as having succeeded optimally, it can be seen from the service per concept (S/C), calving interval (CI) and the level of conception (CR).